2019
DOI: 10.1002/ece3.5553
|View full text |Cite
|
Sign up to set email alerts
|

Exploring taxonomic diversity and biogeography of the family Nemacheilinae (Cypriniformes)

Abstract: Nemacheilidae, in the superfamily Cobitoidea, is comprised of many of morphologically similar fish species that occur in Eurasian water bodies. This large group shows inconsistencies between traditional morphological taxonomy and molecular phylogenetic data. We used mitochondrial genomes, recombinase‐activating gene proteins 1 (RAG1) and the mitochondrial cytochrome c oxidase I gene (COI) to study the phylogenetic relationships among Nemacheilidae species using Bayesian inference and maximum likelihood approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…However, we find that this species is closer to the genus Schistura than Y. jiuchiensis, which represents true Yunnanilus and forms a clade with Paranemachilus and Troglonectes , indicating that Petruichthys is not a synonym of Yunnanilus . According to Sgouros et al (2019) , the genus Schistura is polyphyletic, and Chen et al (2019b) revealed that P. brevis is nested within the Schistura clade. Therefore, more morphological and molecular studies are needed to resolve the taxonomic problems of Petruichthys and Schistura as well as the complex relationships between these nemacheilid tribes.…”
Section: Discussionmentioning
confidence: 99%
“…However, we find that this species is closer to the genus Schistura than Y. jiuchiensis, which represents true Yunnanilus and forms a clade with Paranemachilus and Troglonectes , indicating that Petruichthys is not a synonym of Yunnanilus . According to Sgouros et al (2019) , the genus Schistura is polyphyletic, and Chen et al (2019b) revealed that P. brevis is nested within the Schistura clade. Therefore, more morphological and molecular studies are needed to resolve the taxonomic problems of Petruichthys and Schistura as well as the complex relationships between these nemacheilid tribes.…”
Section: Discussionmentioning
confidence: 99%
“…The T. tibetana genome was retrieved from GenBank (accession number SOYY00000000; Yang X. et al, 2019) and used as the reference. The reference genome was first indexed using the "bwa index" in BWA Version 0.7.17-r1188 (Li, 2013), and then re-sequencing clean reads were aligned to the reference using "bwa mem."…”
Section: Snp Callingmentioning
confidence: 99%
“…Earlier studies in Triplophysa loaches mainly focused on taxonomy (Zhu, 1989;Wu and Wu, 1992;Prokofiev, 2010;Kottelat, 2012), systematics (Wang et al, 2016;Chen et al, 2019;Wang T. et al, 2020), and biogeography (Chen et al, 1992;Wang et al, 2012;Feng et al, 2019;Hu et al, 2020). Next-generation sequencing (NGS) data are now largely adopted to identify molecular signatures of adaptation to high altitude (Wang et al, 2015a;Wang et al, 2015b), cave (Zhao et al, 2020), and salt/alkali (Chen et al, 2020) in Triplophysa loaches with comparative genomic approach, and several Triplophysa genomes have been determined with NGS data (Yang L. et al, 2019;Yang X. et al, 2019;Yuan et al, 2020;Zhou et al, 2021). However, the population genetics and adaptive mechanisms to salinity changes using NGS data have been rarely investigated in Triplophysa loaches (but see Chen et al, 2020;Hu et al, 2020;Yuan et al, 2020;Huo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proko ev performed a detailed comparative morphological analysis [3], which divided Nemacheilidae into ve tribes: Vaillantellini, Lefuini, Yunnanilini, Triplophysini, and Nemacheilini [4,[6][7][8][9][10]. However, the challenges of valid species identi cation exist due to morphological and genetic diversity, especially within the tribe Nemacheilini [9,11]. Besides, the distribution also has led to taxonomic issues, especially in Homatula, Nemacheilus and Schistura [9,11,12].…”
Section: Introductionmentioning
confidence: 99%